Identification and Evaluation of Technical and Operational Parameters of Mobile Positive Pressure Ventilation Fans Used during Rescue Operations - Piotr Kaczmarzyk; Wojciech Klapsa; Paweł Janik; Piotr Krawiec (Safety & Fire Technology, 2021)
Aim: The aim of the article is to indicate the essential technical and operational parameters of mobile fans and to present the proposed testing method- ologies (as well as dedicated infrastructure) allowing to confirm the indicated features. Project and methods: In many places around the world, scientists conduct tests related to the use of mechanical tactical ventilation with the use of mobile positive pressure ventilation fans. These devices are used by fire protection units, among others, for the removal of thermal decomposition products resulting from fires, posing a threat to people staying in construction facilities during events and hindering rescue operations. Achieving the expected effects through the use of mechanical tactical ventilation depends on many factors, among others, on the appropriate technical parameters and the ability to use the fan. Describing the essential features that should be characterized by the devices in question, attention in particular should be paid to: mobility, durability, reliability and effectiveness. To confirm these features, mobile fans should be tested using properly validated test methodologies. This publication presents a draft of the test program that allows to confirm the effectiveness of mobile fans, i.e. aerodynamic efficiency (flow rate), stream shape (area of the effective speed distribution), operating time, noise, weight and dimensions. Conclusions: Mobile fans used by fire protection units are an important tool supporting the effectiveness of rescue operations. However, in order for them to be used in an optimal way, it is necessary to comprehensively examine the technical parameters, and then – adequately to these parameters – to develop appropriate procedures for their use. In the context of the aforementioned testing, despite the large scientific achievements in this field, there are still areas that require improvement, with particular emphasis on standardized testing methodologies and the measurement infrastructure dedicated to them. For this reason, the authors indicated important technical and functional features that determine the effectiveness of mobile fans and recom - mended selected methods on the basis of which these features can be verified. The intention of the project is to provide rescuers with greater comfort when choosing and using the devices in question. The basis for this comfort is to be aware of the availability of equipment with confirmed functional characteristics and the possibility of referring to the developed guidelines for the proper use of fans in accordance with their parameters.